Composite cathode material, preparation method thereof, cathode, battery and electric device
Patent Information
- Application Number
- CN202410268464.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-08
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2044-03-08
AI Technical Summary
但是富锂锰基正极材料的循环稳定性较差,容易恶化电池单体的循环性能和存储性能
Smart Images

Figure CN120613371B_ABST
Abstract
Description
Technical Field
[0001] This application belongs to the field of battery technology, specifically relating to a composite cathode material and its preparation method, cathode, battery, and electrical device. Background Technology
[0002] Lithium-ion batteries have rapidly gained popularity in electric vehicles, 3C electronic products, and energy storage devices due to their advantages such as high energy density and low self-discharge. With the widespread application of lithium batteries, the requirements for their electrochemical performance, such as cycle performance, are also becoming increasingly stringent.
[0003] The cathode material of a lithium-ion battery has a significant impact on the battery's electrochemical performance. For example, lithium-rich manganese-based cathode materials, while contributing to high energy density, also significantly affect the battery's cycle performance. However, lithium-rich manganese-based cathode materials have poor cycle stability, which can easily degrade the cycle and storage performance of individual battery cells. Summary of the Invention
[0004] In view of the above problems, this application provides a composite cathode material and its preparation method, cathode, battery and power device to improve battery cycle performance and storage performance.
[0005] In a first aspect, embodiments of this application provide a composite cathode material, which includes a core and a coating layer. The core contains a lithium-rich manganese-based cathode material. The coating layer covers at least a portion of the surface of the core and includes a perovskite material and a fast ion conductor material.
[0006] Therefore, the embodiments of this application, by coating lithium-rich manganese-based cathode materials with perovskite materials and fast-ion conductor materials, can significantly enhance the modification effect of the coating layer on the lithium-rich manganese-based cathode materials, improve the crystal structure stability of the composite cathode materials, and enhance the interfacial stability between the composite cathode materials and the electrolyte, thereby significantly improving the battery's cycle performance and storage performance, among other electrochemical properties. The combined effect of the perovskite materials and fast-ion conductor materials alters the performance of the coating layer, effectively mitigating oxygen desorption and thus significantly improving the lattice structure stability of the lithium-rich manganese-based cathode materials, thereby enhancing the battery's cycle performance and storage performance. Furthermore, the combined effect of the perovskite materials and fast-ion conductor materials effectively reduces the risk of side reactions between the perovskite materials and active lithium; it also further improves kinetic performance, which is beneficial for improving the battery's first-cycle coulombic efficiency.
[0007] In some embodiments, the mass ratio of perovskite material to core mass, based on the total mass of the composite cathode material, is (0.2 to 0.8):100. By controlling the perovskite material content within this range in the composite cathode material, the deoxidation synergistic effect between the perovskite and the lithium-rich manganese-based cathode material in the core can be improved, thereby further enhancing the stability of the crystal structure of the lithium-rich manganese-based cathode material in the core, significantly improving the cycle performance and storage performance of the composite cathode material. Furthermore, perovskite content within this range can effectively regulate the thickness of the coating layer and the stability of the interface with the electrode liquid, reducing gas generation at the cathode; and the specific capacity of the composite cathode material is increased.
[0008] In some embodiments, the mass ratio of perovskite material to core content is (0.25 to 0.7):100. This range can further improve the cycle performance and storage performance of the battery.
[0009] In some embodiments, the mass ratio of fast ion conductor material to core mass, based on the total mass of the composite cathode material, is (0.05 to 10):100. By controlling the content of fast ion conductor material in the composite cathode material within this range, the synergistic effect between the fast ion conductor material and the lithium-rich manganese-based cathode material in the core can be improved, as can the synergistic effect between the fast ion conductor material and the perovskite material. This further enhances the excellent coating and protective performance of the lithium-rich manganese-based cathode material, thereby further improving the stability of the crystal structure of the lithium-rich manganese-based cathode material in the core, and improving the interfacial stability between the composite cathode material and the electrolyte. This significantly improves the cycle performance and storage performance of the battery, reduces cathode gas production, and also reduces side reactions with active lithium, which is beneficial to improving the first-cycle coulombic efficiency of the battery.
[0010] In some embodiments, the mass ratio of fast ion conductor material to the mass content of the core is (0.1 to 0.5):100. This range can further improve the cycle performance and storage performance of the battery.
[0011] In some embodiments, the perovskite material has a cubic crystal structure. The aforementioned perovskite material exhibits high symmetry and O 2- The transport is isotropic and can act as an oxygen buffer layer to mitigate the oxygen release problem of lithium-rich manganese-based cathode materials, thereby improving the gas generation and interface stability of the materials. In particular, when the perovskite material has an oxygen-deficient cubic phase crystal structure, it can effectively reduce the oxygen release problem of lithium-rich manganese-based cathode materials, thereby improving the gas generation and interface stability of the materials.
[0012] In some embodiments, the perovskite material comprises a compound with the molecular formula ABX3, where A includes one or more elements selected from La, Sr, Ca, Al, Zn, Zr, and K; B includes one or more elements selected from Fe, Ti, Mo, Ga, Ru, Zr, Ir, Co, W, Si, Mn, Nb, Ta, Ge, Cr, and Al; and X includes one or more elements selected from O, F, and Cl.
[0013] In some embodiments, ABX3 includes one or more of LaFeO3, LaTiO3, LaMoO3, LaGaO3, LaRuO3, LaIrO3, LaAlO3, LaGaO3, SrTiO3, SrZrO3, SrCrO3, SrCoO3, SrGeO3, SrMnO3, LaCoO3, ZnTaO3, ZnIrO3, and KNbO3.
[0014] In some embodiments, the total content of elements A and B in the perovskite material in the composite cathode material is between 1500 ppm and 6000 ppm. When the total content of elements A and B in the perovskite material is within the above range, it is beneficial to combine with element X to form an oxygen-deficient cubic phase perovskite structure, which is beneficial to further improve the oxygen release problem of lithium-rich manganese-based cathode materials in high-temperature storage and enhance the structural stability of lithium-rich manganese-based cathode materials.
[0015] In some embodiments, the total content of elements A and B in the perovskite material in the composite cathode material is between 1900 ppm and 5500 ppm. This range can further improve the structural stability of the lithium-rich manganese-based cathode material.
[0016] In some embodiments, the content of element X in the perovskite material in the composite cathode material is between 440 ppm and 1800 ppm. When the content of element X in the perovskite material is within the above range, it is beneficial to form an oxygen-deficient cubic perovskite structure with elements A and B, which is beneficial to further improve the oxygen release problem of lithium-rich manganese-based cathode materials in high-temperature storage and enhance the structural stability of lithium-rich manganese-based cathode materials.
[0017] In some embodiments, the content of element X in the perovskite material in the composite cathode material is between 550 ppm and 1600 ppm. This range can further improve the structural stability of the lithium-rich manganese-based cathode material.
[0018] In some embodiments, the fast ion conductor material has an ionic conductivity of 10. -5 S / cm to 10 -2 S / cm. The aforementioned material can further enhance the migration rate of lithium ions.
[0019] In some embodiments, the fast ion conductor material has an ionic conductivity of 10.-5 S / cm up to 6×10 -3 S / cm. The aforementioned material can further enhance the migration rate of lithium ions.
[0020] In some embodiments, the fast ion conductor material includes one or more of lithium phosphate Li3PO4, lithium borate Li3BO3, lithium sulfate Li2SO4, and lithium silicate Li2SiO3; more optionally, the fast ion conductor material includes one or more of lithium phosphate Li3PO4, lithium sulfate Li2SO4, and lithium silicate Li2SiO3.
[0021] In some embodiments, the content of Li in the fast ion conductor material in the composite cathode material is between 80 ppm and 19,000 ppm. When the content of Li is within the above range, it is beneficial to form a fast ion conductor crystal structure with other elements, providing abundant pathways for the diffusion of lithium ions; and it enhances the binding energy with transition metal ions, thereby improving the structural stability of the lithium-rich manganese-based cathode material.
[0022] In some embodiments, the content of Li in the fast ion conductor material in the composite cathode material is 150 ppm to 1000 ppm; when the content of Li is within the above range, the structural stability of the lithium-rich manganese-based cathode material can be further improved.
[0023] In some embodiments, the total content of P, B, S, and Si elements in the composite cathode material of the fast ion conductor material is between 100 ppm and 28,000 ppm. When the total content of P, B, S, and Si elements is within the above range, it is beneficial to form a fast ion conductor crystal structure with other elements such as Li and O, providing abundant pathways for lithium ion diffusion; and it also enhances the binding energy with transition metal ions, thereby improving the structural stability of the lithium-rich manganese-based cathode material.
[0024] In some embodiments, the total content of P, B, S, and Si elements in the fast ion conductor material in the composite cathode material is between 250 ppm and 1500 ppm. When the total content of P, B, S, and Si elements is within the above range, the structural stability of the lithium-rich manganese-based cathode material can be further improved.
[0025] In some embodiments, lithium-rich manganese-based cathode materials include those with the molecular formula Li[Li] x Ni a Co b Mn c M dThe compounds of O2, wherein x+a+b+c+d=1, x>0, a+b+c+d<1, 0≤b<1, and M includes one or more of Mg, Nb, Cr, Ce, Fe, Ta, Al, V, Ti, Zr, Sn, and Mo. The lithium-rich manganese-based cathode materials shown in these structural formulas exhibit high specific capacity, resulting in composite cathode materials with high specific capacity. Furthermore, they can further enhance the synergistic effect with functional materials in the coating layer, improving the lattice stability of the lithium-rich manganese-based cathode material, further mitigating oxygen release and metal ion dissolution in the composite cathode material, and improving the cycle performance and storage performance of the composite cathode material.
[0026] In some embodiments, the thickness of the coating layer is from 0.05 μm to 1.00 μm. By controlling the thickness of the coating layer within this range, it is possible to improve the oxygen desorption synergistic effect between the perovskite material and / or fast ion conductor material and the lithium-rich manganese-based cathode material in the core, mitigate the dissolution of metal ions, and improve the stability of the crystal structure of the lithium-rich manganese-based cathode material and the stability of the interface with the electrolyte.
[0027] In some embodiments, the dislocation density of the composite cathode material is 1.55 × 10⁻⁶. 11 cm -2 Up to 3.7×10 11 cm -2 By controlling the dislocation density of the composite cathode material within the above-mentioned range, compared with the dislocation density in other ranges, the stacking faults can be reduced relatively significantly, thereby significantly improving the voltage decay problem of the composite cathode material 10 during battery cycling and relatively improving the voltage stability of the composite cathode material.
[0028] In some embodiments, the micro-stress of the composite cathode material is 0.3% to 5.0%; optionally, it is 0.3% to 1.0%. Controlling the micro-stress of the composite cathode material within the above range can significantly improve the balance within or between grains in the composite cathode material, thereby significantly alleviating the stress accumulation phenomenon of composite cathode material particles during charge-discharge cycles, thus improving the stability of the particle structure of the composite cathode material, significantly reducing the occurrence of secondary spherical cracking caused by excessive stress in the composite cathode material, and reducing the fatigue and lattice mismatch of the bulk structure of the composite cathode material during high-temperature cycling.
[0029] In some embodiments, the specific surface area (BET) of the composite cathode material is 0.7 m². 2 / g to 3.8m 2 / g; optional 1.35m 2 / g to 3.0m 2 / g; The specific surface area of the composite cathode material is controlled within the above range. Compared with other ranges of specific surface area, this allows for an appropriate contact area between the composite cathode material particles and the electrolyte. While fully utilizing the high specific capacity of the composite cathode material, it can relatively improve the stability of the contact interface between the composite cathode material and the electrolyte, reduce the side reactions at the contact interface, and thus significantly improve the long-term performance of the composite cathode material, including cycle performance; it can also reduce the amount of gas generated under high-temperature storage.
[0030] In some embodiments, the Dv50 particle size of the composite cathode material is 6.5 μm to 11 μm; optionally, it is 7 μm to 10.5 μm. Controlling the Dv50 particle size of the composite cathode material within the above range can improve the compaction density and structural stability of the composite cathode material particles, and can simultaneously improve other electrochemical properties of the composite cathode material, including initial reversible capacity.
[0031] In some embodiments, a composite cathode material, ascorbic acid, and water are mixed to form a mixture system. The mass content of the composite cathode material is 2.0 wt%, and the mass content of ascorbic acid is 0.2 wt%. The mixture system is then mixed with nitric acid at a volume ratio of 1:2. After mixing, the dissolution amount (DM) of Mn element in the composite cathode material is measured, wherein DM ≤ 140 μg / L, and can be optionally ≤ 80 μg / L. When the dissolution amount of Mn element in the composite cathode material is within the above range, the dissolution amount is relatively small, resulting in higher structural stability and better cycle stability of the lithium-rich manganese-based cathode material, which can effectively improve the cycle performance and storage performance of the battery.
[0032] Secondly, embodiments of this application provide a method for preparing a composite cathode material, including:
[0033] The cathode material particles and functional precursors are mixed to obtain a mixture;
[0034] The mixture is sintered to sinter the functional precursor into a coating layer and coat at least a portion of the surface of the cathode material particles to form a composite cathode material, wherein the coating layer includes a perovskite material and a fast ion conductor material.
[0035] Thirdly, embodiments of this application provide a positive electrode containing a composite positive electrode material according to any embodiment of the first aspect of this application or a composite positive electrode material prepared by the preparation method according to any embodiment of the second aspect of this application.
[0036] Fourthly, embodiments of this application provide a battery including the positive electrode of any embodiment of the third aspect of this application.
[0037] Fifthly, embodiments of this application provide an electrical device including a battery according to any embodiment of the fourth aspect of this application. Attached Figure Description
[0038] Various other advantages and benefits will become apparent to those skilled in the art upon reading the detailed description of the preferred embodiments below. The accompanying drawings are for illustrative purposes only and are not intended to limit the scope of this application. Furthermore, the same reference numerals denote the same parts throughout the drawings. In the drawings:
[0039] Figure 1 This is a schematic diagram of the structure of a composite cathode material according to some embodiments of this application;
[0040] Figure 2 This is a schematic diagram of the structure of the positive electrode in some embodiments of this application;
[0041] Figure 3 This is a schematic diagram of another structure of the positive electrode in some embodiments of this application;
[0042] Figure 4 This is a schematic diagram of the structure of a single battery cell according to an embodiment of this application;
[0043] Figure 5 for Figure 4 The diagram shows an exploded view of a single battery cell.
[0044] Figure 6 This is a schematic diagram of one embodiment of the battery module of this application;
[0045] Figure 7 This is a schematic diagram of one embodiment of the battery pack of this application;
[0046] Figure 8 for Figure 7 The diagram shows the exploded structure of the battery pack.
[0047] Figure 9 This is a schematic diagram of one embodiment of an electrical device that uses a battery as a power source, as described in the present application.
[0048] Figure 10 This is a scanning electron microscope (SEM) image of the composite cathode material of Example 1 of this application.
[0049] The reference numerals in the detailed embodiments are as follows:
[0050] 10. Composite cathode material; 11. Core; 12. Coating layer;
[0051] 20. Positive electrode; 21. Current collector; 22. Active layer;
[0052] 30. Battery cell; 31. Housing; 32. Electrode assembly; 33. Cover plate;
[0053] 40. Battery module;
[0054] 50. Battery pack; 51. Housing; 52. Lower housing. Detailed Implementation
[0055] The embodiments of the technical solution of this application will now be described in detail with reference to the accompanying drawings. These embodiments are only used to more clearly illustrate the technical solution of this application and are therefore merely examples, and should not be used to limit the scope of protection of this application.
[0056] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application pertains; the terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit the application; the terms “comprising” and “having”, and any variations thereof, in the specification, claims, and foregoing description of the drawings are intended to cover non-exclusive inclusion.
[0057] In the description of the embodiments of this application, technical terms such as "first" and "second" are used only to distinguish different objects and should not be construed as indicating or implying relative importance or implicitly specifying the number, specific order, or primary and secondary relationship of the indicated technical features. In the description of the embodiments of this application, "multiple" means two or more, unless otherwise explicitly defined.
[0058] In this document, the term "embodiment" means that a particular feature, structure, or characteristic described in connection with an embodiment may be included in at least one embodiment of this application. The appearance of this phrase in various places throughout the specification does not necessarily refer to the same embodiment, nor is it a separate or alternative embodiment mutually exclusive with other embodiments. It will be explicitly and implicitly understood by those skilled in the art that the embodiments described herein can be combined with other embodiments.
[0059] In the description of the embodiments in this application, the term "and / or" is merely a description of the relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent: A existing alone, A and B existing simultaneously, and B existing alone. Additionally, the character " / " in this document generally indicates that the preceding and following related objects have an "or" relationship.
[0060] In the description of the embodiments of this application, the term "multiple" refers to two or more (including two), similarly, "multiple sets" refers to two or more (including two sets), and "multiple pieces" refers to two or more (including two pieces).
[0061] In the description of the embodiments of this application, the technical terms "center," "longitudinal," "lateral," "length," "width," "thickness," "upper," "lower," "front," "rear," "left," "right," "vertical," "horizontal," "top," "bottom," "inner," "outer," "clockwise," "counterclockwise," "axial," "radial," and "circumferential" indicate the orientation or positional relationship based on the orientation or positional relationship shown in the accompanying drawings. They are only for the convenience of describing the embodiments of this application and simplifying the description, and are not intended to indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation. Therefore, they should not be construed as limitations on the embodiments of this application.
[0062] In the description of the embodiments of this application, unless otherwise expressly specified and limited, technical terms such as "installation," "connection," "joining," and "fixing" should be interpreted broadly. For example, they can refer to a fixed connection, a detachable connection, or an integral part; they can refer to a mechanical connection or an electrical connection; they can refer to a direct connection or an indirect connection through an intermediate medium; they can refer to the internal communication of two components or the interaction between two components. For those skilled in the art, the specific meaning of the above terms in the embodiments of this application can be understood according to the specific circumstances.
[0063] With the rapid application of lithium-ion batteries, especially in electric vehicles, the requirements for the cycle performance of lithium-ion batteries are becoming increasingly stringent.
[0064] The positive electrode is one of the most important components of a battery, containing positive electrode active materials. These active materials have a significant impact on the battery's electrochemical performance, such as cycle performance and energy density.
[0065] The emergence of lithium-rich manganese-based cathode materials has significantly improved the energy density of batteries. However, elements in lithium-rich manganese-based cathode materials may detach from their original lattice positions, making the crystal framework unstable and resulting in poor structural stability, which in turn leads to reduced cycle performance of the battery.
[0066] In related technologies, in order to improve the structural stability of lithium-rich manganese-based cathode materials, a coating layer is usually set on the surface of the lithium-rich manganese-based cathode material to modify it. However, the coating effect is not ideal and cannot effectively improve the structural stability of lithium-rich manganese-based cathode materials.
[0067] To further address the aforementioned issues, this application provides a composite cathode material containing a coating layer. The coating layer comprises a perovskite material and a fast ion conductor material. These materials can enhance the modification effect of the coating layer on the lithium-rich manganese-based cathode material and improve the crystal structure stability of the composite cathode material, thereby significantly improving the electrochemical performance of the battery, including cycle performance and storage performance.
[0068] Composite cathode materials
[0069] In one aspect, embodiments of this application provide a composite cathode material.
[0070] The composite cathode material 10 in this application embodiment has a core-shell structure. In some embodiments, the structure of the composite cathode material 10 in this application embodiment is as follows: Figure 1 As shown, the composite cathode material 10 includes a core 11 and a coating layer 12 covering the core 11. The core 11 contains a lithium-rich manganese-based cathode material, and the coating layer 12 covers at least a portion of the surface of the core 11. The coating layer 12 includes functional materials, including perovskite materials and fast ion conductor materials.
[0071] The core-shell structure of the composite cathode material 10 in this embodiment refers to a core 11 and a shell layer covering the core 11, i.e., a coating layer 12. The coating layer 12 forms a film layer surrounding the surface of the core 11. The core 11 contains lithium-rich manganese-based cathode material, which can be understood as the entire material of the core 11 being lithium-rich manganese-based cathode material. Of course, in addition to containing lithium-rich manganese-based cathode material, it may also contain other components, such as lithium-replenishing materials that are beneficial to improving the capacity of lithium-rich manganese-based cathode material, or additives that can synergistically reduce oxygen release from lithium-rich manganese-based cathode material with the coating layer 12.
[0072] This application embodiment, by coating lithium-rich manganese-based cathode materials with perovskite materials and fast ion conductor materials, can significantly improve the modification effect of the coating layer 12 on the lithium-rich manganese-based cathode materials, improve the crystal structure stability of the composite cathode material 10, and improve the interfacial stability between the composite cathode material 10 and the electrolyte, thereby significantly improving the electrochemical performance of the battery, such as cycle performance and storage performance.
[0073] The possible mechanism of action of the embodiments of this application is speculated to be as follows:
[0074] In related technologies, lithium-rich manganese-based cathode materials exhibit oxygen release, specifically, oxygen on the surface of these materials easily escapes from the crystal lattice, causing instability in the crystal framework and consequently reducing battery cycle performance. Furthermore, the escaped oxygen is highly reactive, reducing the stability of the electrode-electrolyte interface. For example, it can erode the lithium-rich manganese-based cathode material at the electrode-electrolyte interface, leading to an unstable solid-electrolyte interphase (SEI) film and the formation of protons. These protons further erode the material, accelerating these adverse reactions, such as generating gas. In order to alleviate the oxygen release phenomenon of lithium-rich manganese-based cathode materials and further improve the structural and electrochemical stability of lithium-rich manganese-based cathode materials, the embodiments of this application include a perovskite material in the coating layer 12, which enhances the synergistic effect between the coating layer 12 and the lithium-rich manganese-based cathode material. In particular, when the perovskite material has an oxygen-deficient structure, it can effectively reduce the oxygen release problem of lithium-rich manganese-based cathode materials, improve the modification effect of the coating layer 12 on lithium-rich manganese-based cathode materials, significantly alleviate the oxygen release phenomenon of lithium-rich manganese-based cathode materials, improve the crystal structure stability of the composite cathode material 10, and thus significantly improve the electrochemical performance such as cycle performance and storage performance of the battery.
[0075] In related technologies, lithium-rich manganese-based cathode materials suffer from the dissolution of metal ions such as manganese ions. This dissolution leads to instability in the crystal framework, resulting in decreased battery cycle performance. Furthermore, metal ions dissolve from the crystal lattice into the electrolyte and may migrate to the negative electrode surface, damaging the SEI film and further deteriorating cycle performance. In this embodiment, the coating layer 12 includes a fast-ion conductor material. This fast-ion conductor material can bind with metal ions, stabilizing them within the lithium-rich manganese-based cathode material and reducing the risk of metal ion dissolution. This improves the crystal structure stability of the composite cathode material 10, significantly enhancing the battery's electrochemical performance, including cycle performance and storage performance. The fast-ion conductor is ionicly conductive, and the charge carriers can be cations, anions, or ion vacancies, with an ionic conductivity ≥10. -9 The S / cm ratio provides abundant lithium-ion diffusion pathways, which is beneficial for the migration of lithium ions in fast ion conductors. The main bond type of lithium ions in the lattice of fast ion conductors is ionic bond, and the Coulomb attraction between lithium ions and fixed ions in the lattice is relatively small, which is conducive to the rapid migration of lithium ions and further improves the kinetic performance of the battery.
[0076] While perovskite materials can effectively mitigate the oxygen release problem of lithium-rich manganese-based cathode materials, perovskite materials themselves may undergo side reactions with active lithium, resulting in limited or even decreased specific capacity improvement; moreover, the kinetic properties of perovskite materials are relatively poor, which limits the improvement of the kinetic performance of lithium-rich manganese-based cathode materials.
[0077] Furthermore, when the coating layer 12 includes both perovskite and fast-ion conductor materials, the combined effect of these materials alters the performance of the coating layer 12. The coating layer 12 effectively mitigates oxygen desorption, thereby enhancing the lattice structure stability of the lithium-rich manganese-based cathode material and improving the battery's cycle and storage performance. On the other hand, the combined effect of the perovskite and fast-ion conductor materials effectively reduces the risk of side reactions between the perovskite material and active lithium; moreover, it further improves kinetic performance, contributing to a higher first-cycle coulombic efficiency.
[0078] [Lithium-rich manganese-based cathode material]
[0079] In the embodiments, the general molecular formula of the lithium-rich manganese-based cathode material contained in the core 11 of the composite cathode material 10 can be represented as Li[Li x Ni a Co b Mn c M d O2, where x+a+b+c+d=1, x>0, a+b+c+d<1, 0≤b<1, and M includes one or more of Mg, Nb, Cr, Ce, Fe, Ta, Al, V, Ti, Zr, Sn, and Mo. In an exemplary example, the lithium-rich manganese-based cathode material may specifically include Li 1.2 Mn 0.48 Co 0.1 Ni 0.2 Ti 0.02 O2, Li 1.2 Mn 0.48 Co 0.1 Ni 0.2 Zr 0.02 O2, Li 1.2 Mn 0.48 Co 0.1 Ni 0.2 Mo 0.02 O2, Li 1.2 Mn 0.48 Co 0.1 Ni 0.2 V 0.02One or more of O2, etc. The lithium-rich manganese-based cathode materials shown in these structural formulas have high specific capacity, which makes the composite cathode material 10 have high specific capacity. Moreover, it can play a further synergistic role with the functional materials in the coating layer 12, improve the lattice stability of the lithium-rich manganese-based cathode material, further alleviate the oxygen release phenomenon and metal ion dissolution phenomenon of the composite cathode material 10, and improve the cycle performance and storage performance of the composite cathode material 10.
[0080] In the embodiments, the specific capacity of the composite cathode material 10 is from 210 mAh / g to 220 mAh / g, for example, 210 mAh / g, 212 mAh / g, 213 mAh / g, 214 mAh / g, 215 mAh / g, 216 mAh / g, 217 mAh / g, 218 mAh / g, 219 mAh / g, 220 mAh / g, or any range of two of the above values.
[0081] During the charging and discharging process, active ions such as Li are deintercalated and consumed in a single battery cell. The molar content of Li varies when the battery cell is discharged to different states. In the embodiments of this application regarding the composite cathode material 10, the molar content of Li refers to the initial state of the material, i.e., the state before feeding. When the composite cathode material 10 is applied to the battery system, the molar content of Li may change after charge-discharge cycles.
[0082] In the examples of composite cathode material 10 in this application, the molar content of oxygen O is only a theoretical value. Oxygen release from the crystal lattice will cause the molar content of oxygen O to change. In reality, the molar content of oxygen O will fluctuate.
[0083] The core 11 in the composite cathode material 10 can have a regular or irregular morphology. For example, in the exemplary embodiment, the core 11 can be spherical or similar to a sphere, or other morphologies. Furthermore, its particle size and the thickness of the coating layer 12 can jointly influence the particle size of the composite cathode material 10. In the embodiment, the average particle size of the core 11 can be from 5 μm to 11 μm, preferably from 6 μm to 8 μm. In the exemplary embodiment, it can be any two values of 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, or 11 μm, which constitute a typical but non-limiting particle size range. By controlling the particle size of the core 11 within the above range, it is possible not only to increase the content ratio of lithium-rich manganese-based cathode material in the composite cathode material 10, but also to increase the specific capacity of the composite cathode material 10. Furthermore, the particle size range of the core 11, compared to other particle size ranges, allows for a better match between the content of lithium-rich manganese-based cathode material and the functional material in the coating layer 12. This enhances the lattice-stabilizing effect of the coating layer 12 while maintaining a relatively high specific capacity in the composite cathode material 10. It also improves the suppression of oxygen release and / or metal ion dissolution in the lithium-rich manganese-based cathode material, further mitigating capacity decay and improving the cycle performance and electrolyte interface stability of the composite cathode material 10. Additionally, this particle size range of the core 11, together with the coating layer 12, can adjust the particle size of the composite cathode material 10. For example, the Dv50 particle size of the composite cathode material 10 can be 6.5 to 11 μm, thereby improving properties such as compaction density.
[0084] In the embodiments of this application, the average particle size of the core 11 can be calculated using methods and equipment known in the art. For example, a transmission electron microscope (TEM) can be used to scan a cross-sectional photograph of the composite cathode material 10, and then the particle size of the core 11 can be measured. Fifty sample particles can be tested, and the average value can be obtained as the average particle size.
[0085] In the embodiments of this application, the chemical formula and the content of added elements of the composite cathode material 10 can be measured using methods and equipment known in the art. For example, referring to EPA6010D-2014, inductively coupled plasma atomic emission spectrometry (ICP-OES) is used for measurement with an instrument model: Thermo ICAP7400. As an example, the following steps can be followed: First, weigh a certain mass (e.g., 1 g) of the composite cathode material 10 into a beaker, add a certain volume (e.g., 25 mL) of an acid (e.g., HNO3) solution of a certain concentration (e.g., 25% by volume) to the composite cathode material 10 to dissolve it, and dilute it with a certain volume (e.g., 475 mL) of deionized water. Then, place the diluted liquid into the Thermo ICAP7400 instrument for target element analysis calculation, and obtain the content of the target elements and the chemical formula of the composite cathode material 10 through calculation.
[0086] [Perovskite Materials]
[0087] Perovskite materials can be cubic phase crystal structures with the molecular formula ABX3. These perovskite materials exhibit high symmetry and O... 2- The isotropic transport properties allow it to act as an oxygen buffer layer, mitigating oxygen release from lithium-rich manganese-based cathode materials and improving gas generation and interfacial stability. This is especially true when perovskite materials have an oxygen-deficient cubic crystal structure, which effectively reduces oxygen release, thereby improving gas generation and interfacial stability. Furthermore, the chemical stability and acid resistance of these perovskite materials reduce the erosion caused by byproducts in the electrolyte, such as hydrofluoric acid (HF), significantly enhancing the interfacial stability between the lithium-rich manganese-based cathode material and the electrolyte, and improving the cycle stability of the lithium-rich manganese-based cathode material.
[0088] The composite cathode material 10 in this embodiment contains a core 11 with lithium-rich manganese-based cathode material, giving the composite cathode material 10 a high specific capacity. Further, A and B in the ABX3 perovskite can be selected from specific elements. A includes a first element, which may include one or more elements selected from La, Sr, Ca, Al, Zn, Zr, and K. B includes a second element different from the first element, which may include one or more elements selected from Fe, Ti, Mo, Ga, Ru, Zr, Ir, Co, W, Si, Mn, Nb, Ta, Ge, Cr, and Al. X includes one or more elements selected from O, F, and Cl. The ABX3 perovskite has a relatively regular cubic phase perovskite structure with relatively high crystal symmetry. 2-With relatively higher transport isotropy, this specific ABX3 perovskite can better constitute an oxygen buffer layer in the coating layer 12. Because the coating layer 12 can function as a better oxygen buffer, it can significantly suppress oxygen release from the core 11, including the lithium-rich manganese-based cathode material, improving the stability of the crystal structure of the lithium-rich manganese-based cathode material. This effectively alleviates the capacity decay of the lithium-rich manganese-based cathode material, thus significantly improving the cycle performance of the composite cathode material 10. Due to the oxygen-slowing effect of the coating layer 12, it can effectively reduce the amount of oxygen escaping from the composite cathode material 10 into the electrolyte; in addition, the chemical properties of this type of ABX3 perovskite, such as acid resistance, are relatively stable compared to other perovskites, enhancing its resistance to acid corrosion, such as reducing the erosion from the electrolyte by-reaction product HF. Therefore, through the combined effect of the oxygen slow-release effect of the coating layer 12 and its own good chemical stability, the stability of the interface between the positive electrode 20 containing the composite positive electrode material 10 and the electrolyte is effectively improved, the gas generation phenomenon of the positive electrode 20 is reduced, and the reliability of the battery is improved.
[0089] In the embodiments, based on the element types represented by A and B in the ABX3 perovskite contained in the coating layer 12 of the composite cathode material 10 in the above embodiments, the oxidation state of A ion can be +2 or +3, and the oxidation state of B ion can be +3 or +4; the ionic radius r of the element represented by X is... x The ionic radius r of element B B Satisfy r x / r B ≥2.7, 2.7≤(r) A / r B ) / ln(r A / r B )≤3.6. Furthermore, the ionic radius r of element A is... A It can be 70pm≤r A ≤150 pm; Ionic radius r of element B B It can be 40pm≤r B ≤100pm, and r A >r BFurthermore, the sum of the valences of ions A and B can be 6. For example, ABX3 perovskite may include one or more of the following: LaFeO3, LaTiO3, LaMoO3, LaGaO3, LaRuO3, LaMnO3, LaIrO3, LaAlO3, LaGaO3, SrTiO3, SrZrO3, SrCrO3, SrCoO3, SrGeO3, SrMnO3, LaCoO3, ZnTaO3, ZnIrO3, and KNbO3. Further, the ABX3 perovskite may specifically include one or more of LaFeO3, LaTiO3, LaMoO3, LaGaO3, LaRuO3, LaIrO3, LaAlO3, LaGaO3, SrTiO3, SrZrO3, SrCrO3, SrCoO3, SrGeO3, SrMnO3, LaCoO3, ZnTaO3, ZnIrO3, and KNbO3. Optionally, the ABX3 perovskite may specifically include one or more of LaFeO3, LaTiO3, LaMoO3, LaGaO3, LaRuO3, SrTiO3, SrZrO3, LaIrO3, LaAlO3, and LaCoO3.
[0090] The above-mentioned ABX3 perovskites have higher O 2- The high isotropic transport properties and crystal symmetry enhance the oxygen buffering effect of the coating layer 12, thereby improving its oxygen desorption capacity. This further improves the stability of the crystal structure of the lithium-rich manganese-based cathode material, thus mitigating capacity decay and significantly improving the cycle performance of the composite cathode material 10. Furthermore, these types of ABX3 perovskites exhibit stronger acid resistance, further enhancing the stability of the interface between the cathode 20 containing the composite cathode material 10 and the electrolyte, and reducing gas generation at the cathode 20.
[0091] In the embodiments, the mass ratio of ABX3 perovskite to the core 11 in the coating layer 12 of the composite cathode material 10 described above can be (0.2 to 0.8):100, optionally (0.25 to 0.7):100. Typical but non-limiting ratios include 0.2:100, 0.25:100, 0.3:100, 0.4:100, 0.5:100, 0.6:100, 0.7:100, and 0.8:100. The mass ratio of ABX3 perovskite to the core 11 in the coating layer 12 of the composite cathode material 10 described above refers to the ratio of the mass content of the perovskite material to the mass content of the core 11 based on the total mass of the composite cathode material 10.
[0092] By controlling the content of ABX3 perovskite in the composite cathode material 10 within this range, the synergistic effect of ABX3 perovskite and the lithium-rich manganese-based cathode material in the core 11 on slow oxygen desorption can be improved. This further enhances the stability of the crystal structure of the lithium-rich manganese-based cathode material in the core 11, thereby significantly improving the cycle performance and storage performance of the composite cathode material 10. Furthermore, the ABX3 perovskite content within this range can effectively regulate the thickness of the coating layer 12 and the stability of the interface with the electrode liquid, reducing gas generation in the cathode 20; and the specific capacity of the composite cathode material 10 is increased.
[0093] In the embodiments, the total content of elements A and B in the perovskite material in the composite cathode material 10 is 1500 ppm to 6000 ppm, optionally 1900 ppm to 5500 ppm or 1500 to 4500 ppm. In exemplary cases, it can be a typical but non-limiting content range consisting of any two values such as 1500 ppm, 1900 ppm, 2000 ppm, 2500 ppm, 3000 ppm, 3500 ppm, 4000 ppm, 4500 ppm, 5000 ppm, 5500 ppm, and 6000 ppm. When the total content of elements A and B in the perovskite material is within the above range, it is beneficial for them to combine with element X to form an oxygen-deficient cubic perovskite structure, which is beneficial for further improving the oxygen release problem of lithium-rich manganese-based cathode materials during high-temperature storage and enhancing the structural stability of lithium-rich manganese-based cathode materials.
[0094] In the embodiments, the content of element X in the perovskite material in the composite cathode material 10 is 440ppm to 1800ppm, and can be selected as 550ppm to 1600ppm. In the exemplary examples, it can be a typical but non-limiting content range consisting of any two values such as 440ppm, 500ppm, 550ppm, 600ppm, 700ppm, 800ppm, 900ppm, 1000ppm, 1100ppm, 1200ppm, 1300ppm, 1400ppm, 1500ppm, 1600ppm, etc.
[0095] When the content of element X in perovskite materials is within the above range, it is beneficial to form an oxygen-deficient cubic perovskite structure with elements A and B, which is beneficial to further improve the oxygen release problem of lithium-rich manganese-based cathode materials in high-temperature storage and enhance the structural stability of lithium-rich manganese-based cathode materials.
[0096] In the embodiments of this application, the total content of elements A, B, and X in the composite cathode material 10 can be determined using conventional methods for elemental content determination. As an example, referring to EPA6010D-2014, the content is measured by inductively coupled plasma atomic emission spectrometry (ICP-OES) using a Thermo ICAP7400 instrument.
[0097] [Fast Ion Conductor Materials]
[0098] Fast ion conductor materials can enhance abundant lithium-ion diffusion pathways, which is beneficial to improving the migration rate of lithium ions. Moreover, fast ion conductor materials can also combine with transition metal ions and increase oxygen defect formation, which can further alleviate the dissolution of transition metal ions and oxygen.
[0099] Fast ion conductor materials are beneficial for improving the migration rate of lithium ions, especially those with an ionic conductivity ≥10. -9 S / cm, selectable as 10 -9 S / cm to 10 -2 S / cm, selectable as 10 -5 S / cm to 10 -2 S / cm, selectable as 10 -5 S / cm up to 6×10 -3 A conductivity of S / cm can further enhance the migration rate of lithium ions. For example, the ionic conductivity of fast ion conductor materials can reach 10. -9 S / cm, 10 -8 S / cm, 10 -7 S / cm, 10 -6 S / cm, 10 -5 S / cm, 10 -4 S / cm, 10 -3 S / cm, 10 -2 A typical but non-restrictive range consisting of any two values such as S / cm.
[0100] In the embodiments, the fast ion conductor material may include one or more of phosphates, borates, sulfates, and silicates; specifically, the fast ion conductor material includes Li m YO n Y includes one or more elements selected from P, B, S, and Si; m represents the molar amount of Li relative to 1 mol of Y; and n represents the molar amount of O relative to 1 mol of Y. Optionally, Li... m YO nThe fast ion conductor material includes one or more of lithium phosphate (Li3PO4), lithium borate (Li3BO3), lithium sulfate (Li2SO4), and lithium silicate (Li2SiO3). Optionally, the fast ion conductor material may include one or more of phosphates, sulfates, and silicates. The aforementioned fast ion conductor materials can enhance abundant lithium-ion diffusion pathways, which is beneficial for increasing the migration rate of lithium ions. These fast ion conductor materials can also undergo strong binding interactions with metal ions, such as complexation reactions. For example, the anionic ligands in the fast ion conductor material can complex transition metal ions, locking them due to the large binding energy, making migration difficult. This further increases oxygen defect formation, further reducing the dissolution of metal ions and oxygen in the lithium-rich manganese-based cathode material, and improving the lattice structure stability of the lithium-rich manganese-based cathode material. Moreover, the combined effect of the fast ion conductor material and the perovskite material can effectively reduce the risk of side reactions between the coating layer 12 and the active lithium; it can also further improve kinetic performance and enhance the specific capacity of the lithium-rich manganese-based cathode material. In addition, the fast ion conductor material and the perovskite material work together to form the coating layer 12, which can improve the interfacial stability between the composite cathode material 10 and the electrolyte, reduce the risk of side reactions, thereby reducing the gas generation phenomenon of the cathode 20 and improving the reliability of the battery.
[0101] In the embodiments, the mass ratio of fast ion conductor material to core 11 in the coating layer 12 of the composite cathode material 10 in the above embodiments is (0.05 to 10):100, which can be selected as (0.1 to 0.5):100. In exemplary examples, it can be 0.05:100, 0.1:100, 0.15:100, 0.2:100, 0.25:100, 0.3:100, 0.4:100, 0.5:100, 0... The typical but non-restrictive range consisting of any two ratios such as 0.6:100, 0.7:100, 0.8:100, 1:100, 1.2:100, 1.5:100, 2:100, 2.2:100, 2.5:100, 2.8:100, 3:100, 3.2:100, 3.5:100, 3.8:100, 4:100, 4.2:100, 4.5:100, and 5:100.
[0102] The mass ratio of fast ion conductor material to core 11 in the coating layer 12 of the composite cathode material 10 refers to the ratio of the mass content of the fast ion conductor material to the mass content of the core 11 based on the total mass of the composite cathode material 10.
[0103] By controlling the content of fast ion conductor material in the composite cathode material 10 within this range, the synergistic effect between the fast ion conductor material and the lithium-rich manganese-based cathode material in the core 11 can be improved, as can the synergistic effect between the fast ion conductor material and the perovskite material. This further enhances the excellent coating and protective performance of the lithium-rich manganese-based cathode material, thereby further improving the stability of the crystal structure of the lithium-rich manganese-based cathode material in the core 11 and improving the interfacial stability between the composite cathode material 10 and the electrolyte. This significantly improves the cycle performance and storage performance of the battery, reduces the gas production of the cathode 20, reduces the side reaction with active lithium, improves the specific capacity utilization of the lithium-rich manganese-based cathode material, and improves the first-cycle coulombic efficiency of the battery.
[0104] In the embodiments, the content of Li element in the fast ion conductor material in the composite cathode material 10 is 80ppm to 19000ppm, and can be selected as 150ppm to 1000ppm. In the exemplary example, it can be a typical but non-limiting content range consisting of any two values such as 80ppm, 150ppm, 200ppm, 300ppm, 400ppm, 500ppm, 600ppm, 700ppm, 800ppm, 900ppm, 1000ppm, 1100ppm, 1200ppm, 1300ppm, 1400ppm, 1500ppm, 2000ppm, 3000ppm, 4000ppm, 5000ppm, 6000ppm, 7000ppm, 8000ppm, 10000ppm, 11000ppm, 12000ppm, 15000ppm, 16000ppm, 17000ppm, 18000ppm, and 19000ppm. When the content of Li is within the above range, it is beneficial to form a fast ion conductor crystal structure with other elements, providing abundant pathways for the diffusion of lithium ions; and it enhances the binding energy with transition metal ions, thereby improving the structural stability of lithium-rich manganese-based cathode materials.
[0105] In the embodiments, the total content of P, B, S and Si elements in the fast ion conductor material in the composite cathode material 10 is from 100ppm to 28000ppm, and can be selected from 250ppm to 1500ppm. In the exemplary example, it can be a typical but non-limiting content range consisting of any two values such as 100ppm, 500ppm, 1000ppm, 1200ppm, 1500ppm, 2000ppm, 3000ppm, 4000ppm, 4500ppm, 5000ppm, 6000ppm, 7000ppm, 8000ppm, 9000ppm, 10000ppm, 11000ppm, 12000ppm, 13000ppm, 14000ppm, 15000ppm, 20000ppm, 25000ppm, and 28000ppm.
[0106] When the total content of P, B, S, and Si elements is within the above range, it is beneficial to form a fast ion conductor crystal structure with other elements such as Li and O, providing abundant pathways for lithium ion diffusion; and it also enhances the binding energy with transition metal ions, thereby improving the structural stability of lithium-rich manganese-based cathode materials.
[0107] In the embodiments of this application, the total content of Li, P, B, S, and Si elements in the composite cathode material 10 can be determined using conventional methods for elemental content determination. As an example, ICP emission spectroscopy (inductively coupled plasma atomic emission spectrometry) can be used for determination, and the specific test procedure refers to the standard test method EPA6010D-2014.
[0108] In the embodiments, transition metal ions, such as iron ions and manganese ions, may dissolve in the lithium-rich manganese-based cathode material. The dissolution amount of manganese ions is detected to confirm the structural stability of the lithium-rich manganese-based cathode material. Specifically, the dissolution amount DM of Mn element in the composite cathode material 10 is ≤140 μg / L, and can be selected as ≤70 μg / L. In the exemplary example, it can be a typical but non-limiting content range consisting of any two values such as 0 μg / L, 10 μg / L, 20 μg / L, 30 μg / L, 40 μg / L, 50 μg / L, 60 μg / L, 70 μg / L, 80 μg / L, 90 μg / L, 100 μg / L, 110 μg / L, 120 μg / L, 130 μg / L, and 140 μg / L. When the amount of Mn dissolved in the composite cathode material 10 is within the above range, the amount dissolved is relatively small. The lithium-rich manganese-based cathode material has high structural stability and good cycle stability, which can effectively improve the cycle performance and storage performance of the battery.
[0109] The leaching amount of Mn can be tested by the following method: The composite cathode material 10, ascorbic acid and water are mixed into a mixed system, the mass content of the composite cathode material 10 is 2.0 wt% and the mass content of ascorbic acid is 0.2 wt%; the mixed system and nitric acid are mixed at a volume ratio of 1:2, and the leaching amount DM of Mn in the composite cathode material 10 is determined by inductively coupled plasma optical emission spectrometry (ICP-OES).
[0110] Specifically, the process for testing the leaching amount of Mn is as follows:
[0111] ① Weigh 1 ± 0.01 g of sample;
[0112] ② Add 50mL of ultrapure water to a 150mL beaker, add 0.1±0.01g of ascorbic acid powder (VC), and sonicate for 5min until completely dissolved;
[0113] ③ Measure 50 mL of the prepared 0.2 wt% VC solution and add it to another beaker. After adding a magnetic stir bar, seal the beaker and perform magnetic stirring at a speed of 500 rpm. The process is as follows: magnetic stirring for 5 min, standing for 24 min, and magnetic stirring for 1 min.
[0114] ④ Take the stirred solution and filter 4 mL of the filtrate into a test tube;
[0115] ⑤ Add 2 mL of nitric acid to a 100 mL glass volumetric flask, and then take 1 mL of filtrate from the test tube in the previous step and add it to the glass volumetric flask to make up to volume.
[0116] ⑥ Use inductively coupled plasma optical emission spectroscopy (ICP-OES) to test the leaching amount of Mn element, input the dilution factor and the fixed volume / sample mass, and record the experimental results Mn / ppm.
[0117] The above testing process can simulate the dissolution of Mn in batteries under high-temperature storage conditions, thereby reflecting the Mn dissolution situation.
[0118] Based on the core 11 and coating layer 12 contained in the composite cathode material 10 described above, the dislocation density, micro-stress, specific surface area, and particle size of the composite cathode material 10 can be improved by adjusting and controlling the particle size of the core 11 and the material and thickness of the coating layer 12. This further improves the mechanical properties of the composite cathode material 10, including structural strength, and its electrochemical properties, including voltage stability and stability of the interface with the electrolyte.
[0119] In the embodiments, the thickness range of the coating layer 12 can be adjusted by controlling the total content of perovskite material and / or fast ion conductor material in the composite cathode material 10. For example, in the embodiments, the thickness of the coating layer 12 contained in the composite cathode material 10 can be controlled to be 0.05 μm to 1 μm, optionally 0.1 μm to 0.8 μm, and further 0.1 to 0.4 μm. Typical but non-limiting thickness ranges include 0.05 to 0.1 μm, 0.1 to 0.2 μm, 0.2 to 0.3 μm, 0.3 to 0.4 μm, 0.4 to 0.5 μm, 0.5 to 0.6 μm, 0.6 to 0.7 μm, 0.7 to 0.8 μm, 0.8 to 0.9 μm, and 0.9 to 1 μm. By controlling the thickness of the coating layer 12 within this range, the effects of slow oxygen desorption and enhancement between the perovskite material and / or fast ion conductor material and the lithium-rich manganese-based cathode material in the core 11 can be improved, as well as the effect of mitigating metal ion dissolution. This also improves the stability of the crystal structure of the lithium-rich manganese-based cathode material and the stability of the interface with the electrolyte. As shown in the table below, the relevant performance of the batteries in Examples B1 to B4 is superior to that of the batteries shown in Examples B5 and B6. Simultaneously, the high specific capacity of the composite cathode material 10 can also be achieved.
[0120] In this embodiment, the thickness of the coating layer 12 can be determined by scanning a cross-sectional photograph of the coating layer 12 using a transmission electron microscope (TEM) and then measuring the distance between the inner and outer walls of the coating layer 12; alternatively, it can be detected using a scanning electron microscope (SEM) and an electronic spectrometer (EDS). For example, the sample preparation adhesive is mixed evenly with the composite cathode material 10 powder and then coated onto a copper foil to obtain a sample, wherein the weight of the powder is 5 times that of the sample preparation adhesive, and then dried at 60°C for 30 minutes. The prepared sample is cut into 6mm*6mm pieces with scissors, fixed on a sample stage, placed in an ion polishing instrument, and the sample edges are adjusted to be parallel to the centerline X-axis, with the Y-axis position at 40-60μm before cutting. After cutting, an energy dispersive spectroscopy (EDS) combined with a scanning electron microscope (SEM) was used to select a suitable particle section on the cut sample and perform a linear scan of the characteristic element content of the coating layer 12 along the particle diameter direction. The radius of the particle was measured as R, and the distance from the particle center to the site where the element content of the coating layer 12 increases compared to the particle core 11 was L1. Then the thickness L of the coating layer 12 was (R-L1) μm.
[0121] As in the embodiments, the dislocation density of the composite cathode material 10 in the above embodiments can be 1.55 × 10⁻⁶. 11 Up to 3.7×10 11 cm -2 1.8×10 can be selected. 11 Up to 3.2×10 11 cm -2 In the example, it could be 1.55 × 1011 Up to 1.8×10 11 cm -2 1.8×10 11 Up to 2.0×10 11 cm -2 2.0×10 11 Up to 2.5×10 11 cm -2 2.5×10 11 Up to 3.0×10 11 cm -2 3.0×10 11 Up to 3.2×10 11 cm -2 3.2×10 11 Up to 3.5×10 11 cm -2 Typical but not limiting dislocation density ranges are defined. Here, the dislocation density quantifies the number of dislocations contained in the crystal of the composite cathode material 10, specifically referring to the total length of dislocation lines per unit volume of crystal. Controlling the dislocation density of the composite cathode material 10 within the aforementioned range, compared to other dislocation density ranges, can significantly reduce stacking faults, thereby significantly improving the voltage decay problem of the composite cathode material 10 during battery cycling and relatively enhancing the voltage stability of the composite cathode material 10.
[0122] In this embodiment, the dislocation density of the composite cathode material 10 can be calculated using methods and equipment known in the art. For example, a method for detecting the dislocation density of the composite cathode material 10 is based on XRD testing β = (1 / D). 2 ×10 16 Where D = Kλ / Bcosθ, K = 0.9, λ = 1.5406, B is the full width at half maximum (FWHM) of the 10(hkl) crystal plane of the composite cathode material in the XRD diffraction pattern, and θ is the diffraction angle.
[0123] In the embodiments, the micro-stress of the composite cathode material 10 in the above embodiments can be from 0.3% to 5.0%, and can be selected from 0.3% to 1.0%. In the exemplary examples, it can be a typical but non-limiting range of micro-stress consisting of any two values such as 0.3%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, and 5%. Micro-stress refers to the stress acting between the microstructures of the composite cathode material 10, also known as micro-residual stress. Specifically, it refers to the stress existing between or within the grains of the composite cathode material 10 due to factors such as deformation, phase transformation, and expansion of multiphase materials. Controlling the micro-stress of the composite cathode material 10 within the above-mentioned range can significantly improve the balance within or between grains in the composite cathode material 10, thereby significantly alleviating the stress accumulation phenomenon of the composite cathode material 10 particles during charge-discharge cycles, thus improving the stability of the particle structure of the composite cathode material 10, significantly reducing the occurrence of secondary spherical cracking caused by excessive stress in the composite cathode material 10; and reducing the fatigue and lattice mismatch of the bulk structure of the composite cathode material 10 during high-temperature cycling.
[0124] In the embodiments of this application, the micro-stress of the composite cathode material 10 can be calculated using methods and equipment known in the art. For example, fitting can be performed by X-ray diffraction (XRD) testing. As an example, the following steps can be followed: First, set the XRD test conditions: use a Cu target, set the tube voltage (e.g., 40V), set the tube current (e.g., 40mA), set the scan speed (e.g., <2° / min), set the 2θ scan range (e.g., 15°-70°), set the step size (e.g., 0.02°), set the emission slit (DS) (e.g., 1mm), set the anti-scattering slit (SS) (e.g., 8mm), and use a graphite monochromator. The micro-stress obtained by fitting the XRD pattern is: MS=(Bhkl*Cosθhkl) / (4sinθhkl), where θhkl is the diffraction angle of the composite cathode material 10(hkl) crystal plane in the XRD pattern, and Bhkl is the full width at half maximum (FWHM) of the composite cathode material 10(hkl) crystal plane in the XRD pattern.
[0125] In the embodiments, the BET specific surface area of the composite cathode material 10 in the above embodiments can be 0.7 m². 2 / g to 3.8m 2 / g, can be selected as 1.35m 2 / g to 3.0m 2 / g; optional 1.35m 2 / g to 2.3m 2 / g, in the example, can be 0.7m 2 / g, 0.8m 2 / g, 0.9m 2 / g, 1.0m 2 / g, 1.2m 2 / g, 1.35m 2 / g, 1.5m 2 / g, 1.8m 2 / g、2m 2 / g, 2.3m 2 / g, 2.5m 2 / g, 2.8m 2 / g, 3.2m 2 / g, 3.5m 2 / g, 3.8m 2 / g is a typical but not limiting range of specific surface areas. Here, BET specific surface area refers to the total area per unit mass of composite cathode material 10. Controlling the specific surface area of composite cathode material 10 within the above range, compared to other ranges, ensures an appropriate contact area between the composite cathode material 10 particles and the electrolyte. While fully utilizing the high specific capacity of composite cathode material 10, it can relatively improve the stability of the interface between composite cathode material 10 and the electrolyte, reduce side reactions at this interface, and thus significantly improve the long-term performance of composite cathode material 10, including cycle performance. Furthermore, while enhancing the specific capacity utilization of composite cathode material 10, it can also reduce gas generation during high-temperature storage.
[0126] In the embodiments of this application, the BET specific surface area of the composite cathode material 10 can be tested using any known method. For example, the specific surface area of the composite cathode material 10 can be tested with reference to GB / T19587-2017 "Determination of Specific Surface Area of Solid Substances by Gas Adsorption BET Method". As an example, the specific surface area of the composite cathode material 10 is measured using a TriStarII3020 device. The composite cathode material 10 is dispersed in a dispersant, such as ethanol, and sonicated for 30 minutes. The material is then dried in a vacuum drying oven, and finally, the specific surface area of the composite cathode material 10 is measured using a specific surface area analyzer.
[0127] In the embodiments, the composite cathode material 10 described above can be controlled by the particle size of its core 11 and the thickness of its coating layer 12, etc., so that the Dv50 particle size of the composite cathode material 10 can be 6.5 μm to 11 μm, optionally 7 μm to 10.5 μm. In the exemplary example, it can be a typical but non-limiting particle size range composed of any two values such as 6.5 μm, 7 μm, 8 μm, 9 μm, 10 μm, and 11 μm. Controlling the Dv50 particle size of the composite cathode material 10 within the above range can improve the compaction density of the composite cathode material 10 particles and improve the structural stability of the composite cathode material 10 particles, and can also simultaneously improve other electrochemical properties of the composite cathode material 10, including the first reversible capacity.
[0128] In the embodiments of this application, the volume average particle size Dv50 of the material has a well-known meaning in the art. The volume average particle size Dv50 of the material refers to the particle size corresponding to 50% of the volume distribution. It can be detected using equipment and methods known in the art. A certain amount of composite material is taken as a sample, and the volume average particle size Dv50 is tested using a Malvern 300 laser particle size analyzer according to the test standard GB / T19077-2016 / ISO13320:2009 Particle size distribution laser diffraction method.
[0129] Preparation method of composite cathode material
[0130] Secondly, embodiments of this application provide a method for preparing the composite cathode material 10 described in the above embodiments. The composite cathode material 10 of this application includes the following steps:
[0131] Step S10: Mix the cathode material particles with the functional precursor to obtain a mixture;
[0132] Step S20: The mixture is sintered to sinter the functional precursor into a coating layer 12 and coat at least a portion of the surface of the cathode material particles to form a composite cathode material 10, wherein the coating layer 12 includes a perovskite material and a fast ion conductor material.
[0133] The method for preparing the composite cathode material 10 in this application embodiment uses a functional precursor as raw material. A coating layer 12 containing perovskite material and fast ion conductor material is directly formed on the surface of cathode material particles containing lithium-rich manganese-based cathode material, thereby generating the composite cathode material 10 with the core-shell structure described above. Therefore, the cathode material particles, as the core 11, endow the prepared composite cathode material 10 with high electrochemical performance, including specific capacity. The formed coating layer 12 can effectively improve the crystal structure stability of the lithium-rich manganese-based cathode material in the core 11, alleviate the capacity decay of the lithium-rich manganese-based cathode material, and significantly improve the cycle performance of the composite cathode material 10. Moreover, the formed coating layer 12 has stable chemical properties, effectively enhancing the stability of the interface between the prepared composite cathode material 10 and the electrolyte, and reducing gas generation. In addition, the conditions for forming the coating layer 12 on the surface of the cathode material particles in the preparation method of the composite cathode material 10 in this application embodiment are controllable, making the prepared composite cathode material 10 stable in performance and highly efficient, suitable for large-scale industrial production and application.
[0134] Step S10:
[0135] The cathode material particles in step S10 are as follows: Figure 1The composite cathode material 10 shown in the above-described embodiment contains a core 11; therefore, the cathode material particles in step S10 are lithium-rich manganese-based cathode materials. Since the cathode material particles in step 10 are as shown... Figure 1 The core 11 contained in the composite cathode material 10 of the above-described embodiment is shown. Therefore, the components, particle size, etc., of this cathode material particles are the same as those contained in the core 11 of the composite cathode material 10 described above.
[0136] The cathode material particles can be prepared according to the conventional cathode 20 material preparation method, or they can be prepared by modifying the conventional cathode 20 material preparation method. For example, in the demonstration, when the cathode material particles are lithium-rich manganese-based cathode materials, specifically lithium-rich manganese-based cathode material particles, they can be prepared according to the conventional lithium-rich manganese-based cathode material preparation method, or they can be commercially available.
[0137] For example, the preparation method of lithium-rich manganese-based cathode material is as follows: various raw material precursors (such as lithium salts, Me elements, compounds of M elements, etc.) and ball milled zirconium beads are mixed in a drum-type ball mill mixer at a ball-to-material ratio of 25 to 80. The Li / Me molar ratio is 1.3 to 1.4, and Me is the total molar amount of nickel, cobalt, and manganese. The mixture is placed in a muffle furnace for sintering at a sintering temperature of 780°C to 900°C, a heating rate of 2°C / min to 5°C / min, a sintering time of 10h to 15h, and an air sintering atmosphere. After sintering, the material is mechanically ground and sieved to obtain the lithium-rich manganese-based cathode material.
[0138] The functional precursor in step S10 can form the functional material in the coating layer 12 of the composite cathode material 10 in the above-described embodiments. For example, the functional precursor includes a perovskite precursor, which can form the perovskite material in the coating layer 12 of the composite cathode material 10 in the above-described embodiments. The perovskite precursor can be specifically selected based on the type of perovskite material. Specifically, the ABX3 perovskite precursor can be selected based on the type of ABX3 perovskite in the coating layer 12 of the composite cathode material 10 in the above-described embodiments.
[0139] Perovskite precursors can include lanthanum chloride (cation with oxidation state +3), lanthanum nitrate, lanthanum acetate, strontium chloride (cation with oxidation state +2), strontium nitrate, calcium oxide, calcium hydroxide, calcium chloride, calcium sulfate, aluminum fluoride (cation with oxidation state +3), alumina, aluminum sulfate, zinc oxide (cation with oxidation state +2), zinc chloride, zinc nitrate, zinc sulfate, zirconium fluoride (cation with oxidation state +2, +3, or +4), zirconium chloride, titanium chloride, and dioxinium chloride. The precursors selected are one or more of the following: titanium dioxide, titanium nitrate, titanium sulfate, tungsten oxide (cation with a oxidation state of +2), tungstic acid, silicon dioxide, manganese chloride, manganese dioxide, cobalt nitrate, cobalt hydroxide (cation with a oxidation state of +2 or +3), cobalt sulfate, gallium hydroxide (cation with a oxidation state of +3), molybdenum oxide, niobium oxide, lanthanum chlorate, lanthanum cobaltate, lanthanum titanate, zirconium titanate, strontium titanate, ferric oxide, ruthenium oxide, iridium oxide, chromium oxide, germanium oxide, tantalum oxide, and potassium hydroxide. Using these precursors, the sintering process in step S20 can produce the corresponding ABX3 perovskite described above.
[0140] The fast ion conductor precursor can form the fast ion conductor material in the coating layer 12 of the composite cathode material 10 in the embodiments of the above application. The fast ion conductor precursor can be specifically selected based on the type of fast ion conductor material. Specifically, the fast ion conductor precursor can be selected based on the type of fast ion conductor in the coating layer 12 of the composite cathode material 10 in the embodiments of the above application.
[0141] Fast ion conductor precursors may include one or more of lithium phosphate, lithium hydrogen phosphate, lithium borate, boric acid, lithium sulfate, silicon dioxide, and lithium silicate.
[0142] The fast ion conductor precursor and the perovskite precursor are co-sintered and sintered. The fast ion conductor precursor is sintered into a fast ion conductor, and the perovskite precursor is sintered into a perovskite material. The fast ion conductor precursor and the perovskite precursor may also react with each other, which further enhances the synergistic effect between the coating layer and the lithium-rich manganese-based cathode material.
[0143] In the embodiments, the mixing process of the cathode material particles and the functional precursor can be either a dry mixing process or a solution mixing process.
[0144] The dry mixing process can involve directly mixing cathode material particles and functional precursor powders without solvents. In this embodiment, the dry mixing process can involve directly stirring or ball milling the mixture comprising cathode material particles and functional precursors.
[0145] Solution mixing is an alternative to the dry mixing process described above. In the embodiment, the functional precursor is prepared into a solution and then mixed with the cathode material particles to form a slurry. The slurry is then dried to remove the solvent, allowing the functional precursor to form a precursor coating layer 12 that coats the surface of the cathode material particles. Alternatively, the functional precursor and cathode material particles can be mixed with a solvent to form a slurry, which is then dried to remove the solvent, allowing the functional precursor to form a precursor coating layer 12 that coats the surface of the cathode material particles.
[0146] During the mixing process in step S10, the mass content and thickness of the coating layer 12 generated in step S20 can be adjusted by controlling the mixing ratio of the cathode material particles and the functional precursor.
[0147] As in the embodiments, by controlling the mixing ratio of the cathode material particles and the functional precursor, the mass ratio of the cathode material particles to the perovskite precursor in the functional precursor satisfies the mass ratio of the core 11 to the perovskite material in the coating layer 12 of the composite cathode material 10 in the embodiments of the above application, which is 100:(0.2~0.8), or optionally 100:(0.25~0.7). That is, in the embodiments, in step S10, the cathode material particles and the perovskite precursor are mixed according to a mass ratio of cathode material particles to perovskite material of 100:(0.2~0.8), or optionally 100:(0.25~0.7).
[0148] As in the embodiment, the mass ratio of the cathode material particles to the fast ion conductor precursor in the functional precursor satisfies the mass ratio of the core 11 to the fast ion conductor material in the coating layer 12 of the composite cathode material 10 in the above-described embodiment of the application as 100:(0.05-10), optionally 100:(0.1-5). That is, in the embodiment, in step S10, the cathode material particles and the fast ion conductor precursor are mixed according to a mass ratio of cathode material particles to fast ion conductor material of 100:(0.05-10), optionally 100:(0.1-5).
[0149] By controlling the mixing process within the above-mentioned ratio range, the thickness of the coating layer 12 generated in step S20 can be controlled within the range of 0.05 to 1 μm as described above. The content of elements contained in the generated perovskite material and fast ion conductor material can also be within the required range, thereby improving the crystal structure stability of the lithium-rich manganese-based cathode material, enhancing the protective effect of the coating layer 12, and improving the stability of the interface between the composite cathode material 10 and the electrolyte.
[0150] Step 20:
[0151] During the sintering process in step 20, the functional precursor will be sintered to generate the functional material in the coating layer 12 contained in the composite cathode material 10 of the above application embodiment, and can form a coating layer 12 containing perovskite material and fast ion conductor material to coat the cathode material particles.
[0152] In this embodiment, the sintering temperature can be controlled between 500°C and 750°C. This temperature range allows the perovskite precursor to be completely sintered to form a perovskite-containing material, and the fast-ion conductor precursor to be sintered to form a fast-ion conductor, which then coats the cathode material particles. At this sintering temperature, the sintering time should be sufficient; for example, in this embodiment, when the sintering temperature is between 500°C and 750°C, the sintering time is 6 to 10 hours.
[0153] In this embodiment, the sintering process can be controlled to reach the sintering temperature at a heating rate of 2°C / min to 5°C / min. By controlling the heating rate within this range, the growth of perovskite crystals can be effectively regulated, the oxygen buffering effect of the perovskite-containing coating layer 12 can be enhanced, the oxygen release phenomenon of the lithium-rich manganese-based cathode material in the core 11 can be further reduced, and the stability of the interface between the composite cathode material 10 and the electrolyte can be improved.
[0154] In this embodiment, the sintering atmosphere can be air. After sintering, the material is mechanically ground and sieved to obtain composite cathode material 10.
[0155] positive electrode
[0156] Thirdly, embodiments of this application provide a positive electrode 20. In some embodiments, such as Figure 2 and Figure 3 As shown, the positive electrode 20 of this application embodiment includes a current collector 21 and an active layer 22 disposed on at least one side of the current collector 21. The active layer 22 is bonded to the current collector 21. In the positive electrode 20 of this application embodiment, the positive electrode material contained in the active layer 22 includes the composite positive electrode material 10 of the above-described application embodiment.
[0157] Since the positive electrode material contained in the active layer 22 of the positive electrode 20 in this application embodiment includes the composite positive electrode material 10 in the above application embodiment, the positive electrode 20 in this application embodiment not only has high energy density, but also has good cycle performance. Its interface stability with the electrolyte is good, which can effectively reduce gas generation.
[0158] In this embodiment, the current collector 21 included in the positive electrode 20 refers to a structure or component used for collecting current. In the embodiments, the current collector 21 included in the positive electrode 20 includes, but is not limited to, metal current collectors, carbon current collectors, conductive resin current collectors, and composite current collectors of metal and resin, more specifically, copper, nickel, titanium, iron and their respective alloys, stainless steel, carbon fiber, carbon nanotubes (CNTs), graphite, etc. In the embodiments, the current collector 21 can also be a dense film layer or a porous film layer.
[0159] In this embodiment, the active layer 22 of the positive electrode 20 refers to a film layer containing positive electrode material. In the embodiments, the active layer 22 of the positive electrode 20 in this embodiment can be stacked on the surface of the current collector 21. When the surface layer of the current collector 21 has a porous structure or the current collector 21 itself has a porous structure, the active layer 22 can be at least partially embedded in the current collector 21.
[0160] In this embodiment, when the active layer 22 is stacked on the surface of the current collector 21, it can be bonded to one surface of the current collector 21, such as... Figure 2 As shown. When the current collector 21 has two opposing surfaces, that is, when it is a membrane structure, the active layer 22 can be bonded to the two opposing surfaces of the current collector 21, such as... Figure 3 As shown.
[0161] In the embodiments, the active layer 22 of the positive electrode 20 of this application embodiment includes not only the composite positive electrode material 10 of the above-described application embodiment, but also necessary components such as the composite positive electrode material 10 and other components. Other components may include binders or may further include conductive agents, other additives and other components.
[0162] In the embodiments, when the active layer 22 contains an adhesive, the adhesive may include one or more of oil-soluble adhesives, water-soluble adhesives, and emulsion adhesives. In exemplary embodiments, the oil-soluble adhesive may include one or more of polyvinylidene fluoride, polyimide, polytetrafluoroethylene, polybutylene acrylate, and polyacrylonitrile; in exemplary embodiments, the water-soluble adhesive may include one or more of carboxymethyl cellulose, carboxymethyl cellulose salt, polyacrylic acid, polyacrylate, polyvinyl alcohol, sodium alginate, and cyclodextrin; in exemplary embodiments, the emulsion adhesive may include one or more of styrene-butadiene rubber, vinyl acetate resin, acrylic resin, and chlorinated rubber. In some embodiments, the mass percentage of the adhesive is ≤5% based on the total mass of the active layer 22.
[0163] In the embodiments, when the active layer 22 contains a conductive agent, the conductive agent may include one or more of acetylene black (SP), carbon nanotubes, conductive carbon black (super-P), Ketjen black, carbon fiber, graphene, etc. In some embodiments, the mass percentage of the conductive agent is ≤5% based on the total mass of the active layer 22.
[0164] In the embodiments, when the active layer 22 contains other additives, the additives may include, but are not limited to, functional components such as lithium supplementation.
[0165] The specific materials such as the composite cathode material 10, binder, and conductive agent can be selected according to the application or production requirements of the cathode 20.
[0166] The positive electrode 20 of this application embodiment can be prepared according to the conventional preparation method of positive electrode 20, which may include the following steps: preparing a slurry containing the above-mentioned composite positive electrode material 10, binder and solvent, or further containing conductive agent, other additives and other components; forming the slurry on the current collector 21 (wet film); then performing a drying treatment to allow the solvent to evaporate, thereby drying the wet film; and then performing a roll pressing treatment on the dried film layer to form an active layer 22, thereby obtaining the positive electrode 20.
[0167] Battery
[0168] Fourthly, embodiments of this application also provide a battery. The battery of this application embodiment includes a positive electrode 20 and a negative electrode, wherein the positive electrode 20 is the same as the positive electrode 20 described in the previous application embodiment.
[0169] Since the battery of this application embodiment contains the positive electrode 20 of the above application embodiment, the battery of this application embodiment has good cycle performance, low gas production, and relatively high safety, in addition to having high energy density and other electrochemical performance.
[0170] In the embodiments, the negative electrode contained in the battery of this application embodiment can be a conventional negative electrode, such as in the embodiment, it can be a negative electrode that matches the positive electrode 20 of this application embodiment.
[0171] [negative electrode]
[0172] In some embodiments, the negative electrode includes a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector and comprising a negative electrode active material. For example, the negative electrode current collector has two surfaces opposite each other in its thickness direction, and the negative electrode film layer is disposed on either or both of the two opposite surfaces of the negative electrode current collector.
[0173] The negative electrode active material may be any negative electrode active material known in the art for use in battery cells. As an example, the negative electrode active material may include, but is not limited to, one or more of natural graphite, artificial graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, and lithium titanate. Silicon-based materials may include one or more of elemental silicon, silicon oxide, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. Tin-based materials may include one or more of elemental tin, tin oxide, and tin alloys.
[0174] In some embodiments, the negative electrode film layer may optionally include a negative electrode conductive agent. This application does not impose particular limitations on the type of negative electrode conductive agent. As an example, the negative electrode conductive agent may include one or more of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers. In some embodiments, the mass percentage of the negative electrode conductive agent is ≤5% based on the total weight of the negative electrode film layer.
[0175] In some embodiments, the negative electrode film layer may optionally include a negative electrode binder. This application does not impose particular limitations on the type of negative electrode binder. As an example, the negative electrode binder may include one or more of the following: styrene-butadiene rubber (SBR), water-soluble unsaturated resin SR-1B, waterborne acrylic resins (e.g., polyacrylic acid PAA, polymethacrylic acid PMAA, sodium polyacrylate PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), and carboxymethyl chitosan (CMCS). In some embodiments, the mass percentage of the negative electrode binder is ≤5% based on the total weight of the negative electrode film layer.
[0176] In some embodiments, the negative electrode film may optionally include other additives. As an example, other additives may include thickeners, such as sodium carboxymethyl cellulose (CMC-Na), PTC thermistor materials, etc. In some embodiments, the mass percentage of other additives is ≤2% based on the total weight of the negative electrode film.
[0177] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. As an example of a metal foil, copper foil may be used. The composite current collector may include a polymer substrate and a metal material layer formed on at least one surface of the polymer substrate. As an example, the metal material may include one or more of copper, copper alloys, nickel, nickel alloys, titanium, titanium alloys, silver, and silver alloys. As an example, the polymer substrate may include one or more of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), and polyethylene (PE).
[0178] The negative electrode film is typically formed by coating a negative electrode slurry onto a negative electrode current collector, followed by drying and cold pressing. The negative electrode slurry is usually formed by dispersing the negative electrode active material, optional conductive agent, optional binder, and other optional additives in a solvent and stirring until homogeneous. The solvent can be N-methylpyrrolidone (NMP) or deionized water, but is not limited to these.
[0179] The negative electrode does not exclude other additional functional layers besides the negative electrode film layer. For example, in some embodiments, the negative electrode of this application further includes a conductive undercoat layer (e.g., composed of a conductive agent and an adhesive) sandwiched between the negative electrode current collector and the negative electrode film layer and disposed on the surface of the negative electrode current collector. In other embodiments, the negative electrode of this application further includes a protective layer covering the surface of the negative electrode film layer.
[0180] Of course, in addition to the electrodes and other components described above, the battery in this application embodiment may also include other necessary or auxiliary components. For example, when the battery in this application embodiment is an ion battery, it includes components or parts such as a separator and an electrolyte.
[0181] [Septum]
[0182] A battery cell also includes a separator.
[0183] In some embodiments, the battery cell also includes a separator. This application does not impose any particular limitation on the type of separator; any known porous separator with good chemical and mechanical stability can be selected.
[0184] In some embodiments, the diaphragm material may include one or more of glass fiber, nonwoven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The diaphragm may be a single-layer film or a multi-layer composite film, without particular limitation. When the diaphragm is a multi-layer composite film, the materials of each layer may be the same or different, without particular limitation.
[0185] Electrolyte
[0186] During the charging and discharging process of a single battery cell, active ions repeatedly insert and extract between the positive and negative electrodes, while the electrolyte acts as a conductor for these active ions. This application does not impose any particular restrictions on the type of electrolyte; it can be selected according to actual needs.
[0187] Electrolytes consist of electrolyte salts and solvents. The types of electrolyte salts and solvents are not specifically limited and can be selected according to actual needs.
[0188] As an example, the electrolyte salt may include, but is not limited to, one or more of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalate borate (LiDFOB), lithium dioxalate borate (LiBOB), lithium difluorophosphate (LiPO2F2), lithium difluorodioxalate phosphate (LiDFOP), and lithium tetrafluorooxalate phosphate (LiTFOP).
[0189] As an example, the solvent may include, but is not limited to, one or more of ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butyl ester carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), methyl ethyl sulfone (EMS), and diethyl sulfone (ESE).
[0190] In some embodiments, the electrolyte may optionally include additives. For example, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery performance, such as additives that improve battery overcharge performance, additives that improve battery high-temperature performance, and additives that improve battery low-temperature power performance.
[0191] In the embodiments, the batteries in the above embodiments may include any one of battery cells, battery modules, and battery packs.
[0192] Here, a battery cell refers to the battery casing and the electrode assembly (also known as a bare cell) encapsulated within the casing. There are no particular limitations on the shape of the battery cell; it can be cylindrical, square, or any other arbitrary shape. In the example, the battery cell can be as follows: Figure 4 The shown is a square-structured battery cell 30.
[0193] In some embodiments, such as Figure 5As shown, the outer packaging of the battery cell 30 may include a housing 31 and a cover plate 33. The housing 31 may include a bottom plate and side plates connected to the bottom plate, the bottom plate and side plates forming a receiving cavity. The housing 31 has an opening communicating with the receiving cavity, and the cover plate 33 is used to cover the opening to close the receiving cavity. The positive electrode 20, separator and negative electrode contained in the battery cell 30 of this application embodiment may be formed into an electrode assembly 32 by a winding process and / or a stacking process. The electrode assembly 32 is encapsulated in the receiving cavity. Electrolyte is immersed in the electrode assembly 32. The number of electrode assemblies 32 contained in the battery cell 30 may be one or more, which can be adjusted according to actual needs.
[0194] In some embodiments, the battery cell 30 can be prepared by assembling the positive electrode 20, separator, negative electrode, and electrolyte of the above-described embodiments to form the battery cell 30. As an example, the positive electrode 20, separator, and negative electrode of the above-described embodiments can be formed into an electrode assembly 32 through a winding or stacking process. The electrode assembly 32 is placed in an outer packaging, dried, and then injected with electrolyte. After vacuum sealing, settling, formation, and shaping processes, the battery cell 30 is obtained. Since the battery cell 30 contains the positive electrode 20 of the above-described embodiments...
[0195] In the embodiments, when the battery in the present application is a battery module, the battery module refers to the assembly of the battery cells 30, that is, it can contain multiple battery cells 30, and the specific number can be adjusted according to the application and capacity of the battery module.
[0196] In some embodiments, Figure 6 This is a schematic diagram of battery module 40 as an example. Figure 6 As shown, in the battery module 40, multiple battery cells 30 can be arranged sequentially along the length of the battery module 40. Of course, they can also be arranged in any other manner. Furthermore, the multiple battery cells 30 can be fixed in place using fasteners.
[0197] Optionally, the battery module 40 may also include a housing with a receiving space in which multiple battery cells 30 are received.
[0198] A battery pack refers to an assembly of the aforementioned battery cells 30, meaning it can contain multiple battery cells 30. These multiple battery cells 30 can be assembled into the aforementioned battery module 40. The specific number of battery cells 30 or battery modules 40 contained in the battery pack can be adjusted according to the application and capacity of the battery pack.
[0199] As in the example, Figure 7 and Figure 8This is a schematic diagram of a battery pack 50 as an example. The battery pack 50 may include a battery compartment and multiple battery modules 40 disposed within the battery compartment. The battery compartment includes an upper compartment 51 and a lower compartment 52. The upper compartment 51 covers the lower compartment 52, forming a closed space for accommodating the battery modules 40. The multiple battery modules 40 can be arranged in any manner within the battery compartment.
[0200] Electrical appliances
[0201] Fifthly, this application also provides an electrical device. The electrical device of this application includes a power supply unit or an energy storage unit, and may also include other auxiliary or necessary components. The power supply unit or energy storage unit contains the battery described in the above application embodiment. The power supply unit or energy storage unit may contain one or more batteries. When there are multiple batteries, they can form a battery module or battery pack. Because the electrical device of this application embodiment contains the battery described in the above application embodiment, the power supply unit or energy storage unit of the electrical device of this application embodiment has high energy density, good cycle performance, long service life, and high safety. Furthermore, the electrical device of this application embodiment has long standby or battery life and high safety in use.
[0202] Figure 9 This is a schematic diagram of an example electrical device. The device could be a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. To meet the device's requirements for high power and high energy density, a battery pack or battery module can be used.
[0203] Another example of an electrical device could be a mobile phone, tablet, or laptop. These devices typically require a slim and lightweight design and can use rechargeable batteries as their power source.
[0204] In the embodiments, when the electrical device includes an energy storage unit, the electrical device can be an energy storage device, which includes the energy storage unit and may also include other auxiliary or necessary components. The energy storage unit contains the battery described in the above-described embodiment. The energy storage unit may contain one or more batteries. When there are multiple batteries, they can form a battery module or battery pack. Because the energy storage device of this embodiment includes the battery described in the above-described embodiment, the energy storage device has high energy density, good cycle performance, long service life, and high safety.
[0205] Example
[0206] The following describes embodiments of this application. The embodiments described below are exemplary and are only used to explain this application, and should not be construed as limiting this application. Where specific techniques or conditions are not specified in the embodiments, they are performed according to the techniques or conditions described in the literature in this field or according to the product instructions. Reagents or instruments used, unless otherwise specified, are all conventional products that can be obtained commercially.
[0207] Example 1
[0208] Composite cathode materials and their preparation methods
[0209] This embodiment provides a composite cathode material and its preparation method. The composite cathode material of this embodiment includes lithium-rich manganese-based cathode material particles, with a coating layer on the surface of the particles. This coating layer contains LaAlO3 and Li3PO4. The relevant parameters of the lithium-rich manganese-based cathode material particles and the coating layer are shown in the table below.
[0210] The preparation method of composite cathode materials includes the following steps:
[0211] S1. Preparation of lithium-rich manganese-based cathode material particles: according to the molecular formula Li 1.17 Mn 0.58 Ni 0.24 Ti 0.01 The molar ratio of elements contained in the O2 lithium-rich manganese-based cathode material was accurately weighed as follows: Li2CO3 lithium salt, MnSO4·H2O manganese salt, CoSO4·7H2O cobalt salt, and TiO2 precursor compounds were weighed out. These precursor compounds were then mixed with zirconium balls at a ratio of 60:1 in a drum-type ball mill mixer to obtain a precursor mixture. This precursor mixture was then sintered in a muffle furnace at 800℃, a heating rate of 2℃ / min, and a sintering time of 10 h in an air atmosphere. After sintering, the material was mechanically ground and sieved to obtain the molecular formula Li. 1.17 Mn 0.58 Ni 0.24 Ti 0.01 O2-rich lithium-manganese-based cathode material particles;
[0212] S2. Preparation of perovskite coating layer on the surface of lithium-rich manganese-based cathode material particles:
[0213] The perovskite precursor material aluminum sulfate and the fast ion conductor precursor material lithium hydrogen phosphate were mixed in a drum ball mill for 10 hours. Then, the lithium-rich manganese-based cathode material particles obtained from S1 were added to the drum ball mill and mixed again for 10 hours. After mixing, the mixture was placed in a muffle furnace for sintering at a temperature of 700℃, a heating rate of 3℃ / min, and a sintering time of 9 hours. The sintering atmosphere was air. After sintering, the material was mechanically ground and sieved to obtain a composite cathode material of perovskite-coated lithium-rich manganese-based cathode material.
[0214] Examples 2 to 4
[0215] The positive electrodes provided in Examples 2 to 4 differ from those in Example 1 in that the mass ratio of perovskite material to core is adjusted.
[0216] Examples 5 to 8
[0217] The positive electrodes provided in Examples 5 to 8 differ from those in Example 1 in that the mass ratio of the fast ion conductor material to the core is adjusted.
[0218] Examples 9 to 13
[0219] The positive electrodes provided in Examples 9 to 13 differ from those in Example 1 in that the type of perovskite material was adjusted.
[0220] Examples 14 to 16
[0221] The positive electrodes provided in Examples 14 to 16 differ from those in Example 1 in that the material of the fast ion conductor is adjusted.
[0222] Comparative Example 1
[0223] The positive electrode provided in Comparative Example 1 differs from that in Example 1 in that it does not have a coating layer.
[0224] Comparative Example 2
[0225] The positive electrode provided in Comparative Example 2 differs from that in Example 1 in that the coating layer includes a fast ion conductor.
[0226] Comparative Example 3
[0227] The positive electrode provided in Comparative Example 3 differs from that in Example 1 in that the coating layer includes a perovskite material.
[0228] Positive electrode, battery example
[0229] This embodiment provides a positive electrode and a battery cell (full cell) containing the positive electrode. The battery cell in this embodiment includes an electrode assembly formed by a positive electrode, a separator, and a negative electrode, and also includes an electrolyte. The positive electrode contains the composite positive electrode material described in the above embodiment.
[0230] Preparation of the positive electrode: The composite positive electrode material from the above embodiment was premixed in a stirring tank for 30 minutes, then the conductive agent acetylene black (SP) and the binder polyvinylidene fluoride (PVDF) were added for a second dry mixing for 30 minutes. Then, the solvent N-methylpyrrolidone (NMP) was added and the mixture was rapidly stirred under vacuum to form a slurry. The mass ratio of composite positive electrode material:acetylene black:polyvinylidene fluoride was 96:2:2, and the solid content of the slurry was 70% by weight. The slurry was uniformly coated on both sides of a 12 μm thick aluminum foil. The coated electrode was dried in an oven at 100-130℃ for half an hour and then removed. The positive electrode material loading of the electrode was 21.5 mg / cm³. 2 The extracted positive electrode is cold-pressed through rollers to obtain the positive electrode.
[0231] Preparation of the negative electrode: The negative electrode materials artificial graphite, hard carbon, conductive agent acetylene black, binder styrene-butadiene rubber (SBR), and thickener sodium carboxymethyl cellulose (CMC) are thoroughly mixed in a deionized water solvent system at a weight ratio of 90:5:2:2:1. The mixture is then coated onto copper foil, dried, and cold-pressed to obtain the negative electrode.
[0232] Separator: A porous polyethylene polymer film with a thickness of 12 μm.
[0233] Electrolyte: 1 mol / L lithium salt LiPF6, solvent including EC+EMC+DMC in a volume ratio of 1:1:1.
[0234] Battery cell: The positive electrode, separator, and negative electrode are stacked in sequence, with the separator positioned between the positive and negative electrodes to provide isolation, and then wound to obtain the bare cell; the bare cell is placed in an outer package, injected with the prepared basic electrolyte, and sealed to obtain a full cell.
[0235] Full cell performance testing:
[0236] (1) Battery gas generation detection method:
[0237] Full cells at 100% State of Charge (SOC) were stored at 60°C. The open-circuit voltage (OCV) and internal resistance (IMP) were measured before, during, and after storage to monitor SOC, and the cell volume was also measured. Every 48 hours after storage, the full cells were removed, allowed to stand for 1 hour, and then OCV and IMP were tested. After cooling to room temperature, the cell volume was measured using the water displacement method. The water displacement method involves first measuring the cell's weight (F1) separately using a balance with automatic unit conversion, and then completely immersing the cell in deionized water (with a known density of 1 g / cm³). 3 In the experiment, the weight of the battery F2 is measured at this time, and the buoyancy force F_buoyancy on the battery is F1-F2. Then, according to Archimedes' principle F_buoyancy = ρgV_displaced, where V_displaced is the volume of water displaced, the battery volume V = V_displaced = (F1-F2) / ρg is calculated.
[0238] After each volume test, the battery is recharged by charging it to 4.45V with a constant current of 0.5C, and then charged at a constant voltage of 4.45V until the current drops to 0.05C. After the recharge is completed, the battery is put into the furnace for further testing.
[0239] After 30 days of storage, the battery volume was measured, and the ratio of the increase in battery volume after storage to the battery capacity, i.e., the unit gas production rate mL / Ah, was calculated relative to the battery volume before storage.
[0240] (2) Cycle retention rate of individual cells (%):
[0241] Using a single full-cell battery as the test object, under a constant temperature environment of 25℃, the battery was charged to 4.45V at a rate of 0.5C at a voltage of 2.5V to 4.45V. Then, it was charged at a constant voltage of 4.45V until the current was ≤0.05mA. After resting for 5 minutes, it was discharged to 2.5V at a rate of 0.2C. The discharge capacity was recorded. The previous process was repeated to obtain the capacity retention rate after a specified number of cycles, such as 500 cycles. The capacity retention rate = discharge capacity in the first cycle / discharge capacity at the specified number of cycles × 100%.
[0242] (3) Testing methods for determining the storage performance of individual battery cells:
[0243] Under a constant temperature environment of 25℃, let it stand for 5 minutes, discharge at 1 / 3C to 2.5V, let it stand for 5 minutes, charge at 1 / 3C to 4.5V, and then charge at 4.5V at a constant voltage until the current is ≤0.05mA. Let it stand for 5 minutes. The charging capacity at this time is recorded as C0. Then discharge at 1 / 3C to 2.8V. The discharge capacity at this time is the initial specific capacity, recorded as D0.
[0244] Then, the battery was charged from 0.33C constant current to 4.5V and constant voltage until the current ≤0.05mA. After standing for 5 minutes, it was placed in a high and low temperature chamber at 60℃ and left to stand for 1 hour until the battery temperature reached the target temperature before storage. After 15 days, it was taken out and the previous process was repeated in a constant temperature environment at 25℃. The capacity Dn (n=0,1,2……) was recorded every 15 days. The capacity retention rate after 60 days of storage was calculated as: (D4-D0) / D0*100%.
[0245] Test Results
[0246] The test results are shown in Tables 1 to 4.
[0247] Table 1
[0248]
[0249] In Table 1,
[0250] In Comparative Example 1, the composite cathode material is a core-based lithium manganese cathode material with the molecular formula Li. 1.17 Mn 0.58 Ni 0.24 Ti 0.01 O2.
[0251] The composite cathode materials in Comparative Examples 2 and 3, and Examples 1 to 16, include a core and a coating layer. The molecular formula of the core lithium-manganese-based cathode material is Li. 1.17 Mn 0.58 Ni 0.24 Ti 0.01 O2.
[0252] The initial specific capacity of the composite cathode material in Comparative Example 1 was 214.5 mAh / g, and the initial specific capacity of the composite cathode material in Comparative Example 3 was 210.3 mAh / g. In Comparative Example 3, the perovskite material may undergo side reactions with active lithium, resulting in a slight deterioration in specific capacity. In Example 1, the coating layer includes perovskite material and fast ion conductor material. The combined effect of the two can reduce the risk of side reactions between perovskite material and active lithium, further improve kinetic performance, increase specific capacity, and help improve the first-cycle coulombic efficiency of the battery. The initial specific capacity of the composite cathode material in Example 1 was 216.6 mAh / g.
[0253] The composite cathode material of this application embodiment has an appropriate range of dislocation density, micro-stress and specific surface area, which makes the composite cathode material of this application embodiment have good mechanical properties such as particle structure strength, and improves electrochemical properties such as voltage stability and stability of the interface with electrolyte.
[0254] Table 2
[0255]
[0256] As shown in Table 2,
[0257] Comparative Example 1: The lithium-rich manganese-based cathode material did not have a coating layer on its surface, resulting in relatively poor cycle performance and storage performance, and a high amount of gas generated during storage.
[0258] Compared to Comparative Example 1, Comparative Example 2 has a coating layer on the surface of lithium-rich manganese-based cathode material, the coating layer including fast ion conductors; Comparative Example 3 has a coating layer on the surface of lithium-rich manganese-based cathode material, the coating layer including perovskite material, which improves the performance of composite cathode materials to a certain extent and can enhance the storage performance and cycle performance of battery cells, but the improvement effect is not significant.
[0259] Compared to Comparative Example 2, where the coating layer only contained fast ion conductors, and Comparative Example 3, where the coating layer only contained perovskite material, Examples 1 to 16 simultaneously deposited fast ion conductor material and perovskite material on the surface of lithium-rich manganese-based cathode material. The resulting battery cells exhibited relatively higher storage and cycle performance, and relatively lower gas production. As shown in Figure 10, Figure 10 The image shown is a scanning electron microscope (SEM) image of the composite cathode material in Example 1. The composite cathode material has a uniform surface coating, which can play an excellent protective role against lithium-rich manganese-based cathode materials and improve their performance.
[0260] By adjusting the mass ratio of perovskite material to the core, the oxygen release problem of lithium-rich manganese-based cathode materials can be further improved, and the stability of the crystal structure of lithium-rich manganese-based cathode materials can be enhanced. In particular, when the mass ratio of perovskite material to core is 0.2:100 to 0.8:100, and can be further selected as 0.25:100 to 0.8:100, the oxygen release problem can be further improved. When it can be further selected as 0.25:100 to 0.70:100, the oxygen release problem of composite cathode materials is significantly improved.
[0261] By adjusting the mass ratio of fast ion conductor material to the core, the combined effect of fast ion conductor material and perovskite material can further improve the storage and cycle performance of the battery cell. In particular, when the mass ratio of fast ion conductor material to core is 0.05:100 to 10:100, and can be further selected as 0.1:100 to 10:100, the storage and cycle performance can be further improved, and the gas production can be further reduced. When it can be further selected as 0.1:100 to 0.5:100, the storage and cycle performance can be further improved.
[0262] By controlling at least one of the types of perovskite materials and the materials of fast ion conductors, the storage performance and cycle performance of battery cells can be further improved.
[0263] Examples 17 and 18
[0264] The positive electrodes provided in Examples 17 and 18 differ from those in Example 1 in that the material of the core body is adjusted.
[0265] Examples 19 and 20
[0266] The difference between the positive electrodes provided in Examples 19 and 20 and those in Example 1 is that the Dv50 of the composite positive electrode material was adjusted.
[0267] Table 3
[0268]
[0269] Table 4
[0270]
[0271] As shown in Tables 3 and 4, by adjusting the particle size Dv50 of the core material and composite cathode material, the cycle performance and storage performance of the battery cell can be improved to a certain extent, and the gas production can be controlled.
[0272] Although illustrative embodiments have been demonstrated and described, those skilled in the art should understand that the above embodiments should not be construed as limiting the present application, and that changes, substitutions and modifications can be made to the embodiments without departing from the spirit, principles and scope of the present application.
Claims
1. A composite cathode material, characterized in that, include: The core contains lithium-rich manganese-based cathode material; as well as A coating layer is applied to at least a portion of the surface of the core. The coating layer comprises a perovskite material and a fast ion conductor material. The perovskite material has a cubic crystal structure and a molecular formula of ABX3. The fast ion conductor material comprises one or more of phosphates, borates, sulfates, and silicates.
2. The composite cathode material according to claim 1, characterized in that, Based on the total mass of the composite cathode material, the ratio of the mass content of the perovskite material to the mass content of the core is (0.2 to 0.8):
100.
3. The composite cathode material according to claim 2, characterized in that, The ratio of the mass content of the perovskite material to the mass content of the core is (0.25 to 0.7):
100.
4. The composite cathode material according to any one of claims 1 to 3, characterized in that, Based on the total mass of the composite cathode material, the ratio of the mass content of the fast ion conductor material to the mass content of the core is (0.05 to 10):
100.
5. The composite cathode material according to claim 4, characterized in that, The ratio of the mass content of the fast ion conductor material to the mass content of the nucleus is (0.1 to 0.5):
100.
6. The composite cathode material according to any one of claims 1 to 3, characterized in that, The perovskite material comprises a compound with the molecular formula ABX3, where A includes one or more elements selected from La, Sr, Ca, Al, Zn, Zr, and K; B includes one or more elements selected from Fe, Ti, Mo, Ga, Ru, Zr, Ir, Co, W, Si, Mn, Nb, Ta, Ge, Cr, and Al; and X includes one or more elements selected from O, F, and Cl.
7. The composite cathode material according to claim 6, characterized in that, The ABX3 includes one or more of the following: LaFeO3, LaTiO3, LaMoO3, LaGaO3, LaRuO3, LaIrO3, LaAlO3, SrTiO3, SrZrO3, SrCrO3, SrCoO3, SrGeO3, SrMnO3, LaCoO3, ZnTaO3, ZnIrO3, and KNbO3.
8. The composite cathode material according to any one of claims 1 to 3, characterized in that, The total content of elements A and B in the perovskite material in the composite cathode material is 1500 ppm to 6000 ppm; or The content of element X in the perovskite material in the composite cathode material is 440 ppm to 1800 ppm.
9. The composite cathode material according to claim 8, characterized in that, The total content of elements A and B in the perovskite material in the composite cathode material is 1900 ppm to 5500 ppm; or The content of element X in the perovskite material in the composite cathode material is 550 ppm to 1600 ppm.
10. The composite cathode material according to any one of claims 1 to 3, characterized in that, The fast ion conductor material has an ionic conductivity of 10. -5 S / cm to 10 -2 S / cm.
11. The composite cathode material according to claim 10, characterized in that, The fast ion conductor material has an ionic conductivity of 10. -5 S / cm up to 6×10 -3 S / cm.
12. The composite cathode material according to any one of claims 1 to 3, characterized in that, The fast ion conductor material includes one or more of lithium phosphate (Li3PO4), lithium borate (Li3BO3), lithium sulfate (Li2SO4), and lithium silicate (Li2SiO3).
13. The composite cathode material according to claim 12, characterized in that, The content of Li element in the fast ion conductor material in the composite cathode material is 80 ppm to 19000 ppm; or The total content of P, B, S and Si elements in the fast ion conductor material in the composite cathode material is from 100 ppm to 28000 ppm.
14. The composite cathode material according to claim 13, characterized in that, The content of Li element in the fast ion conductor material in the composite cathode material is 150 ppm to 1000 ppm; or The total content of P, B, S and Si elements in the fast ion conductor material in the composite cathode material is 250 ppm to 1500 ppm.
15. The composite cathode material according to any one of claims 1 to 3, characterized in that, The lithium-rich manganese-based cathode material includes materials with the molecular formula Li[Li] x Ni a Co b Mn c M d Compounds of O2, wherein x+a+b+c+d=1, x>0, a+b+c+d<1, 0≤b<1, and M includes one or more of Mg, Nb, Cr, Ce, Fe, Ta, Al, V, Ti, Zr, Sn and Mo.
16. The composite cathode material according to any one of claims 1 to 3, characterized in that, The thickness of the coating layer is from 0.05 μm to 1.00 μm.
17. The composite cathode material according to any one of claims 1 to 3, characterized in that, The composite cathode material satisfies one or more of the following conditions. (1) The dislocation density of the composite cathode material is 1.55 × 10⁻⁶. 11 cm -2 Up to 3.7×10 11 cm -2 ; (2) The micro-stress of the composite cathode material is 0.3% to 5.0%; (3) The specific surface area (BET) of the composite cathode material is 0.7 m². 2 / g to 3.8m 2 / g; (4) The particle size of the composite cathode material is 6.5 μm to 11 μm.
18. The composite cathode material according to claim 17, characterized in that, The composite cathode material satisfies one or more of the following conditions. (1) The micro-stress of the composite cathode material is 0.3% to 1.0%; (2) The specific surface area (BET) of the composite cathode material is 1.35 m². 2 / g to 3.0m 2 / g; (3) The particle size of the composite cathode material is 7 μm to 10.5 μm.
19. The composite cathode material according to any one of claims 1 to 3, characterized in that, The composite cathode material, ascorbic acid, and water are mixed to form a mixture system, wherein the mass content of the composite cathode material is 2.0 wt% and the mass content of the ascorbic acid is 0.2 wt%. The mixture system and nitric acid were mixed at a volume ratio of 1:
2. After mixing, the amount of Mn dissolved in the composite cathode material, DM, was measured. DM≤140μg / L.
20. The composite cathode material according to claim 19, characterized in that, DM≤80μg / L.
21. A method for preparing a composite cathode material, characterized in that, include: The cathode material particles and functional precursors are mixed to obtain a mixture; The mixture is sintered to sinter the functional precursor into a coating layer, which coats at least a portion of the surface of the cathode material particles to form a composite cathode material. The coating layer comprises a perovskite material and a fast ion conductor material. The perovskite material has a cubic crystal structure and a molecular formula of ABX3. The fast ion conductor material comprises one or more of phosphates, borates, sulfates, and silicates.
22. A positive electrode, characterized in that, The composite cathode material comprising any one of claims 1 to 20 or the composite cathode material prepared by the preparation method described in claim 21.
23. A battery, characterized in that, Includes the positive electrode as described in claim 22.
24. An electrical appliance, characterized in that, Includes the battery as described in claim 23.
Citation Information
Patent Citations
A method for coating a perovskite structural material on that surface of a positive electrode particle
CN109244438A
Composite positive electrode material as well as preparation method and application thereof
CN115241449A